Sulfonamide inhibition study of the β-class carbonic anhydrase from the caries producing pathogen Streptococcus mutans. Issue 11 (1st June 2015) - Dedeoglu, Nurcan; DeLuca, Viviana; Isik, Semra; Yildirim, Hatice; Kockar, Feray; Capasso, Clemente; Supuran, Claudiu T.
Graphical abstract: Abstract: Streptococcus mutans, the oral pathogenic bacterium provoking dental caries formation, encodes for a β-class carbonic anhydrase (CA, EC 4.2.1.1), SmuCA. This enzyme was cloned, characterized and investigated for its inhibition profile with the major class of CA inhibitors, the primary sulfonamides. SmuCA has a good catalytic activity for the CO2 hydration reaction, with a k cat of 4.2 × 10 5 s −1 and k cat / K m of 5.8 × 10 7 M −1 × s −1, and is efficiently inhibited by most sulfonamides ( K I s of 246 nM–13.5 μM). The best SmuCA inhibitors were bromosulfanilamide, deacetylated acetazolamide, 4-hydroxymethylbenzenesulfonamide, a pyrimidine-substituted sulfanilamide derivative, aminobenzolamide and compounds structurally similar to it, as well as acetazolamide, methazolamide, indisulam and valdecoxib. These compounds showed inhibition constants ranging between 246 and 468 nM. Identification of effective inhibitors of this enzyme may lead to pharmacological tools useful for understanding the role of S. mutans CAs in dental caries formation, and eventually the development of pharmacological agents with a new mechanism of antibacterial action.